2019
DOI: 10.1016/j.neuroimage.2019.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Change detection to tone pairs during the first year of life – Predictive longitudinal relationships for EEG-based source and time-frequency measures

Abstract: Brain responses related to auditory processing show large changes throughout infancy and childhood with some evidence that the two hemispheres might mature at different rates. Differing rates of hemispheric maturation could be linked to the proposed functional specialization of the hemispheres in which the left auditory cortex engages in analysis of precise timing information whereas the right auditory cortex focuses on analysis of sound frequency. Here the auditory change detection process for rapidly present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
(109 reference statements)
0
6
0
Order By: Relevance
“…Methods for the auditory exposure paradigm, EEG–ERP recordings, source localization, and electrophysiological and statistical analyses used in this study closely follow those reported in previous publications from the Infancy Studies Laboratory as the same techniques, paradigms, and equipment are in use across studies ( Hämäläinen et al. 2011 , 2019 ; Ortiz-Mantilla et al. 2012 , 2013 , 2016 , 2019 , 2022 ; Musacchia et al.…”
Section: Methodsmentioning
confidence: 93%
“…Methods for the auditory exposure paradigm, EEG–ERP recordings, source localization, and electrophysiological and statistical analyses used in this study closely follow those reported in previous publications from the Infancy Studies Laboratory as the same techniques, paradigms, and equipment are in use across studies ( Hämäläinen et al. 2011 , 2019 ; Ortiz-Mantilla et al. 2012 , 2013 , 2016 , 2019 , 2022 ; Musacchia et al.…”
Section: Methodsmentioning
confidence: 93%
“…As rise time is a dynamic measure based on changes reflecting the shape of the sound pressure wave, it cannot be compared in a simple way to other measures in the infant literature used to index temporal processing, such as duration perception or gap detection. For example, infant studies related to rapid auditory processing theory as a mechanism underpinning DLD and dyslexia ( Tallal, 1980 ) have established that by 6 months of age, some infants can detect a gap between two tones that is as short as 70 ms ( Hämäläinen et al, 2019 ). Data from individual tones of this nature are not comparable to the rise time measure used here.…”
Section: Discussionmentioning
confidence: 99%
“…Infants utilise a range of acoustic cues to aid language learning. The neural literature shows that they are sensitive to rapidly-arriving pitch information ( Hämäläinen et al, 2019 ), changes in duration ( Richardson et al, 2003 ), F0 changes, and features like voice onset time ( Guttorm et al, 2005 , Guttorm et al, 2010 , Leppänen et al, 2010 , van Zuijen et al, 2013 ). The incoming stream of speech contains multiple such acoustic features that offer cues to its linguistic structure.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in theta phase synchrony during processing of speech and nonspeech signals over the first year of life ( Ortiz-Mantilla et al. 2016 ; Hämäläinen et al. 2019 ) is thought to represent the more competent processing achieved with brain maturation and native language exposure.…”
Section: Discussionmentioning
confidence: 99%
“…2016 ). Over the same period, intertrial phase synchrony in the theta range also decreases when infants process tone pairs with a speech-like, 70-ms interstimulus interval (ISI) ( Hämäläinen et al. 2019 ), suggesting that neural pathways and auditory perceptual abilities strengthen over development ( Watson et al.…”
Section: Introductionmentioning
confidence: 99%